La biblia en los catecismos (I) - Resines, Luis (Estudio agustiniano, 2021)
The teaching proceeded by reading some selected catechims may possible to see the very variable importance attributed to the Bible in the task of communicating the faith. There are all possibilities: from the most sincere value, to the absolute silence. In the most number of non selected catechims, the Bible is practically uncited. This reflexion shows how the spanish catholics have lived back-wards the word of God.